Preparation method of RuO2 / graphene composite cellulose aerogel electrode material

By adopting the preparation method of RuO2/graphene composite cellulose aerogel electrode material, the problem of low conductivity and porosity of the liquid flow battery electrode material is solved, which significantly improves the conductivity and porosity, improves the energy output efficiency of the battery and reduces the contact resistance.

CN119812374APending Publication Date: 2025-04-11RUISHENG FLOW BATTERY TECHNOLOGY (QINGDAO) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510002284.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing liquid flow battery electrode materials have low mass loading active substances, low porosity and poor conductivity, which leads to uneven mass transfer when the electrolyte flows through the electrode, reducing the energy efficiency and life of the stack.

Method used

The preparation method of RuO2/graphene composite cellulose aerogel electrode material is adopted to generate rich pore structures through high temperature treatment, which significantly improves conductivity and porosity. The biomass material cellulose is used as the substrate to introduce active sites to prepare a self-supported electrode material.

Benefits of technology

The conductivity and porosity of the electrode material are significantly improved, the mass transfer uneven phenomenon when the electrolyte flows through the electrode is avoided, the concentration polarization of the battery is reduced, thereby improving the battery energy output at a given power, and reducing the contact resistance by 30-50%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a RuO2 / graphene composite cellulose aerogel electrode material, and belongs to the field of flow batteries. Graphene composite cellulose carbon aerogel is prepared by a'mixing-gelling-pyrolysis' method; then preparing a RuO2 / graphene composite cellulose aerogel electrode material by taking the graphene composite cellulose carbon aerogel as a conductive substrate and adopting a hydrothermal method; the electrode material is subjected to high-temperature treatment to generate a richer pore structure, so that the conductivity is remarkably improved; cellulose is used as a substrate of an electrode material, and metal and alloy thereof can be firmly deposited; graphene and cellulose synergistically play a role, so that the hybrid material composed of graphene and cellulose has more excellent electrical and thermal conductivity, mechanical properties, optical properties and other characteristics and functionality; ruO2 has good conductivity and electrochemical performance; the aerogel avoids the phenomenon of non-uniform mass transfer when the electrolyte flows through the interior of the electrode, and concentration polarization of the battery is reduced, so that the energy output of the battery under given power is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of liquid flow battery technology, and more particularly to a RuO 2 Preparation method of cellulose / graphene composite aerogel electrode material. Background Art

[0002] In the future, renewable clean energy will gradually replace traditional energy. As an indispensable part of the renewable clean energy system, the energy storage system plays a supporting role in the entire new power generation industry. Renewable clean power generation energy (wind energy, solar energy, etc.) is intermittent and volatile, and it is difficult to continuously output stable and safe electricity. Therefore, energy storage technology is crucial as a connecting part of renewable clean energy. In large-scale energy storage systems, flow batteries (redox flow batteries) can decouple the relationship between energy and power, and the market application prospects are very broad.

[0003] As one of the key materials of liquid flow batteries, the main function of electrodes is to provide a reaction site for active substances, promote the active substances in the electrolyte to transfer electrons at the electrode-electrolyte interface, realize the conversion between electrical energy and chemical energy, and ultimately complete the storage or release of energy; in addition, the electrode also acts as a conductive circuit, ensuring that carriers are transferred in the form of ions and electrons on the electrode surface, thereby ensuring that the battery forms a complete closed conductive circuit; the material properties of the electrode directly affect the electrochemical reaction rate, the internal resistance of the battery, and the distribution uniformity and diffusion state of the electrolyte, which in turn affects the power density and energy conversion efficiency of the battery. Chemical stability also directly affects the service life of the battery.

[0004] The electrode material of liquid flow batteries is usually porous carbon felt or graphite felt. During the long-term operation of liquid flow batteries, the voids in the carbon felt are relatively large, and the electrode reaction area provided is limited. After being assembled into a battery stack, the porosity of the carbon felt or graphite felt changes in the thickness direction due to the compression force on both sides. The porosity on both sides is much smaller than the porosity at the center. The uneven porosity will cause the flow rate and resistance of the electrolyte at the center of the electrode and on both sides of the surface to be very different. This will cause many problems in the liquid flow battery stack, such as uneven electrolyte distribution, uneven electrochemical reaction, uneven current transfer and heat transfer, which will reduce the energy efficiency and life of the battery stack.

[0005] The electrodes of the flow battery are in contact with the electrolyte and need to have good corrosion resistance, excellent electrochemical activity and stability. In order to further improve the electrochemical performance of the electrode material, metal catalysts such as bismuth and iron can be deposited on the surface of the electrode material. Patent CN116779883B discloses a bismuth-doped all-vanadium flow battery electrode and a preparation method thereof. In this process, a carbon-based material is immersed in a resin solution containing a bismuth compound and then subjected to a carbonization treatment to obtain a bismuth-doped all-vanadium flow battery electrode. However, the existing technology has the disadvantages that the metal species loaded on the carbon-based material are easy to fall off and the loading amount is difficult to control, resulting in low electrochemical activity of the electrode. In addition, the electrode material may cause the pore structure to collapse under high temperature conditions, thereby destroying the electrode material. The pore structure is reduced to reduce the porosity; Patent CN102110820A discloses a zinc-bromine redox flow battery positive electrode and a preparation method thereof, including a carbon-plastic composite material plate, that is, a catalyst layer with a high specific surface area is attached to the surface of one side of the carbon-plastic composite material plate, and the catalyst layer is composed of a binder of chlorinated polypropylene or chlorinated polyethylene, a catalyst of activated carbon or carbon-supported metal, and a conductive agent of conductive graphite or carbon black; in actual applications, in order to increase the loading amount of active substances, it is usually achieved by increasing the thickness of the catalyst layer. On the one hand, due to the high content of adhesive in the catalyst layer, the conductivity is poor, and increasing the thickness will further reduce the conductivity; on the other hand, the outer catalyst layer has a dense structure and a small amount of active site exposure. Even if the loading amount of active substances is increased by increasing the thickness of the catalyst layer, its utilization rate is still low.

[0006] Aerogel materials have structural characteristics such as low density, high specific surface area, high porosity and high pore volume, combining the stable electrical properties of graphene and the excellent mechanical properties of cellulose into porous aerogels; metal oxide doping and heteroatom doping are methods to solve the problem of low specific capacitance of electrode materials. Summary of the invention

[0007] The purpose of this application is to provide a RuO 2 The invention discloses a method for preparing a graphene composite cellulose aerogel electrode material, so as to solve the technical problems that the conductive matrix of the existing electrode material has low active substance loading quality, low porosity, poor conductivity, and uneven mass transfer when the electrolyte flows through the inside of the electrode.

[0008] In order to achieve the above purpose, the technical solution adopted in this application is: to provide a RuO 2 The preparation method of graphene composite cellulose aerogel electrode material specifically comprises the following steps:

[0009] (i) preparing a cellulose solution: adding cellulose to a pre-cooled cellulose solution and stirring to obtain a cellulose solution;

[0010] (ii) preparing a graphene oxide / cellulose aerogel composite material: adding a graphene oxide dispersion to a cellulose solution after ultrasonic treatment to obtain a mixed solution, pouring the mixed solution into a mold and freezing it, then adding deionized water into the mold to form a hydrogel, and quickly freezing and drying the hydrogel to obtain a graphene oxide / cellulose aerogel composite material;

[0011] (iii) preparing graphene composite cellulose carbon aerogel: carbonizing the graphene oxide / cellulose aerogel composite material, cleaning it with a cleaning agent and then drying it to obtain the graphene composite cellulose carbon aerogel;

[0012] (IV) Preparation of RuO 2 / graphene composite cellulose aerogel electrode material: RuCl 3 Add to the mixture of distilled water and anhydrous ethanol to obtain RuCl 3 solution, adding graphene composite cellulose carbon aerogel to RuCl 3 The solution was added, the pH was adjusted, the precipitate was collected by centrifugation, the precipitate was washed, and the washed precipitate was dried and calcined to obtain RuO 2 / graphene composite cellulose aerogel electrode material.

[0013] In one embodiment,

[0014] Step (i) The cellulose dissolving solution is prepared by mixing NaOH, urea and deionized water in a mass ratio of 7:12:81.

[0015] In one embodiment,

[0016] In step (i), the mass ratio of cellulose to cellulose dissolving solution is 0.5-5:100, and the precooling temperature is -12°C; preferably, the mass ratio of cellulose to cellulose dissolving solution is 2:100.

[0017] In one embodiment,

[0018] Step (ii) The method for preparing the graphene oxide dispersion is to oxidize graphite using an improved Hummers method, wherein graphite powder, NaNO 3 The powder was stirred evenly with concentrated sulfuric acid and phosphoric acid in an ice bath, and then KMnO was slowly added. 4 Stirring was continued for 3 h; the solution was stirred in a 40 °C water bath for 2 h; distilled water was then added, the temperature was raised to 98 °C and stirring was continued for 0.5 h, cooled to room temperature, and H 2 O 2until the solution turns bright yellow; the product is centrifuged and washed with 10% HCl and distilled water, precipitated until the pH value of the solution is close to 7, and the obtained graphene oxide is dissolved in distilled water and treated with a 300W ultrasonic cleaning machine for 60 minutes to obtain a graphene oxide dispersion with a concentration of 0.204-16.32 mg / ml; preferably, the concentration of the graphene oxide dispersion is 5 mg / ml.

[0019] In one embodiment,

[0020] In step (ii), the mass ratio of the graphene oxide dispersion to the cellulose solution is 0.0001-0.008:1, preferably, the mass ratio of the graphene oxide dispersion to the cellulose solution is 0.0012:1; the ultrasonic time is 20 minutes, the freezing temperature is -20°C, and the freezing time is 12 hours.

[0021] In one embodiment,

[0022] The mass ratio of the mixed solution in step (ii) to deionized water is 1:10; the deionized water needs to be replaced every 2 hours, and replaced 5 times.

[0023] In one embodiment,

[0024] Step (ii) drying is performed by freeze drying, and the drying time is 48 hours.

[0025] In one embodiment,

[0026] The specific steps of step (iii) carbonization are as follows: placing the graphene oxide / cellulose aerogel composite material in a tubular furnace, heating the temperature to 700° C. at a heating rate of 5° C. / min under nitrogen protection, and carbonizing for 2 h; the cleaning agent is composed of hydrochloric acid and deionized water.

[0027] In one embodiment,

[0028] Step (IV) RuCl 3 RuCl in solution 3 The concentration of graphene composite cellulose carbon aerogel and RuCl 3 The mass ratio of the solution is 0.001-0.03:1. Preferably, graphene composite cellulose carbon aerogel and RuCl 3 The mass ratio of the solution is 0.01:1.

[0029] In one embodiment,

[0030] In step (iv), the pH adjusting agent is 0.3 Mmol potassium hydroxide solution, and the pH needs to be adjusted to 7; the washing agent is a combination of distilled water and anhydrous ethanol; the drying temperature is 60° C. and the time is 12 h; the calcination temperature is 200° C.

[0031] The present application provides a RuO 2 / A method for preparing a graphene composite cellulose aerogel electrode material. The electrode material is subjected to high temperature treatment to produce a more abundant pore structure, which can not only optimize the structure and increase the porosity, but also significantly improve the conductivity and the specific surface area of ​​the material. The biomass material cellulose is used as the substrate of the electrode material, and active sites are introduced to prepare a self-supporting electrode material. The surface is rich in active groups, and metals and their alloys can be firmly deposited. Compared with commercially prepared foam nickel, foam copper, foam iron and other electrode materials, the biomass substrate has the advantages of abundant reserves, easy processing, biodegradability, internal natural microchannels and a large number of functional groups. Making it into an electrode material is more conducive to large-scale industrial production. Graphene has many excellent properties such as ultra-high current density, ultra-high carrier mobility, chemical inertness, extremely high thermal conductivity, excellent light transmittance, super hydrophobicity, ultra-high mechanical strength, etc. At the same time, graphene and cellulose have a significant synergistic effect, which can produce an obvious one plus one greater than two effect, so that the hybrid material composed of the two has more excellent electrical and thermal conductivity, mechanical properties and optical properties and other characteristics and functionality; RuO 2 It has good electrical conductivity and electrochemical properties, and can provide a large specific surface area and electrical capacity. During the synthesis process, the aerogel maintains the original skeleton structure, and by regulating the pore structure of the biomass aerogel, increasing the porosity and the specific surface area of ​​the material, the electrical conductivity is significantly improved. The electrode has good mechanical properties, which avoids uneven mass transfer when the electrolyte flows through the electrode, reduces the concentration polarization of the battery, and thus increases the battery energy output at a given power, and reduces the contact resistance by 30-50%. DETAILED DESCRIPTION

[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clear, the present application is further described in detail. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0033] Example 1

[0034] A RuO 2 The preparation method of graphene composite cellulose aerogel electrode material specifically comprises the following steps:

[0035] (i) Preparation of cellulose solution: NaOH, urea and deionized water were prepared into 100 g of cellulose solution in a mass ratio of 7:12:81, magnetic stirring was turned on, 2 g of cellulose was added to the cellulose solution precooled to -12°C, and stirred to form a uniformly dispersed cellulose solution;

[0036] (ii) Preparation of graphene oxide / cellulose aerogel composites: 50 mL of 2.4 mg / mL graphene oxide dispersion was added to the cellulose solution after ultrasonic treatment for 20 min to obtain a mixed solution, the mixed solution was poured into a mold and frozen at -20°C for 12 h, and deionized water was added to the mold to form a hydrogel, the mass ratio of the mixed solution to deionized water in the mold was 1:10, and the deionized water was replaced every 2 h for 5 times; the hydrogel was quickly frozen with liquid nitrogen, and dried in a freeze dryer for 48 h to obtain a graphene oxide / cellulose aerogel composite;

[0037] The preparation method of graphene oxide dispersion is as follows: 5g graphite powder, 3g NaNO 3 The powder was stirred evenly with 125 mL of concentrated sulfuric acid and 15 mL of phosphoric acid in an ice bath, and then 20 g of KMnO was slowly added. 4 Continue stirring for 3 h; continue stirring the solution in a 40 °C water bath for 2 h, at which point the solution turns into a viscous brown liquid; then add 230 mL of distilled water, raise the temperature to 98 °C, continue stirring for 0.5 h, cool to room temperature, and then add 50 mL of H 2 O 2 until the solution turns bright yellow; the product is centrifuged and washed with 10% HCl and distilled water, and precipitated until the pH value of the solution is close to 7, and the obtained graphene oxide is dissolved in distilled water and treated with a 300W ultrasonic cleaning machine for 60 minutes to obtain a graphene oxide dispersion with a concentration of 5 mg / ml;

[0038] (III) Preparation of graphene composite cellulose carbon aerogel: placing the graphene oxide / cellulose aerogel composite material in a tubular furnace, heating it to 700°C at a heating rate of 5°C / min under nitrogen protection, carbonizing it for 2h, repeatedly washing it with 1M hydrochloric acid and deionized water until it is neutral, and then drying it to obtain graphene composite cellulose carbon aerogel;

[0039] (IV) Preparation of RuO 2 / graphene composite cellulose aerogel electrode material: 0.05 mol of RuCl 3 Add to a mixture of 25 mL of distilled water and 25 mL of anhydrous ethanol to prepare 0.1 M RuCl 3 Solution, 0.1g of graphene composite cellulose carbon aerogel was added to 10g of RuCl 3 The solution was stirred for 12 h, the pH was adjusted to 7 with 0.3 M potassium hydroxide solution, the precipitate was collected by centrifugation, the precipitate was washed with distilled water and anhydrous ethanol respectively, the washed precipitate was dried in an oven at 60 ° C for 12 h, and calcined at 200 ° C to obtain RuO 2 / graphene composite cellulose aerogel electrode material with a porosity of 95%.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that the mass ratio of cellulose to cellulose dissolving solution is 0.5:100, and the other operations are the same.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the mass ratio of cellulose to cellulose dissolving solution is 3:100, and the other operations are the same.

[0044] Example 4

[0045] The difference between this embodiment and embodiment 1 is that the mass ratio of cellulose to cellulose dissolving solution is 5:100, and the other operations are the same.

[0046] Example 5

[0047] The difference between this embodiment and embodiment 1 is that the preparation method of the graphene oxide aqueous dispersion is as follows: 0.20g of graphite powder, 0.12g of NaNO 3 The powder was stirred evenly with 5.1 mL of concentrated sulfuric acid and 0.61 mL of phosphoric acid in an ice bath, and then 0.82 g of KMnO was slowly added. 4 Stirring was continued for 3 h; the solution was stirred in a 40 °C water bath for 2 h; then 9.38 mL of distilled water was added, the temperature was raised to 98 °C and stirring was continued for 0.5 h, cooled to room temperature, and then 2.04 mL of H 2 O 2 until the solution turns bright yellow; the product is centrifuged and washed with 10% HCl and distilled water, and precipitated until the pH value of the solution is close to 7, the obtained graphene oxide is dissolved in distilled water and treated with a 300W ultrasonic cleaner for 60 minutes to obtain a graphene oxide dispersion with a concentration of 0.204 mg / ml; the mass ratio of the graphene oxide dispersion to the cellulose solution is 0.0001:1, and the rest of the operations are the same.

[0048] Example 6

[0049] The difference between this embodiment and embodiment 1 is that the preparation method of the graphene oxide aqueous dispersion is as follows: 16.32g of graphite powder, 9.79g of NaNO 3 The powder was stirred evenly with 408 mL of concentrated sulfuric acid and 48.96 mL of phosphoric acid in an ice bath, and then 65.28 g of KMnO was slowly added. 4 After continuous stirring for 3 h, the solution turned dark green. After continuous stirring for 2 h in a 40 °C water bath, the solution turned into a viscous brown liquid. Then, 750.72 mL of distilled water was added to the solution, the temperature was raised to about 98 °C, stirring was continued for 0.5 h, cooled to room temperature, and then 163.20 mL of H 2 O 2until the solution turns bright yellow; the product is centrifuged and washed with 10% HCl and distilled water, and precipitated until the pH value of the solution is close to 7, the obtained graphene oxide is dissolved in distilled water and treated with a 300W ultrasonic cleaner for 60 minutes to prepare a graphene oxide dispersion with a concentration of 16.32 mg / ml; the mass ratio of the graphene oxide dispersion to the cellulose solution is 0.008:1, and the rest of the operations are the same.

[0050] Example 7

[0051] The difference between this embodiment and embodiment 1 is that the graphene composite cellulose carbon aerogel and RuCl 3 The mass ratio of the solution was 0.001:1, and the rest of the operations were the same.

[0052] Example 8

[0053] The difference between this embodiment and embodiment 1 is that the graphene composite cellulose carbon aerogel and RuCl 3 The mass ratio of the solution was 0.03:1, and the rest of the operations were the same.

[0054] The present application provides a RuO 2 The method for preparing a graphene / cellulose aerogel composite electrode material comprises the following steps: preparing a cellulose solution, preparing a graphene oxide / cellulose aerogel composite material, preparing a graphene composite cellulose carbon aerogel, preparing RuO 2 / graphene composite cellulose aerogel electrode material; the electrode material produces a richer pore structure after high temperature treatment, with a porosity of 93-97%. This method can not only optimize the structure and increase the porosity, but also significantly improve the conductivity and the specific surface area of ​​the material, which is conducive to the penetration of electrolytes; the biomass material cellulose is used as the substrate of the electrode material, and active sites are introduced to prepare a self-supporting electrode material with abundant active groups on the surface, which can firmly deposit metals and their alloys; compared with commercially prepared nickel foam, copper foam, iron foam and other electrode materials, the biomass substrate has storage Graphene has many advantages such as abundant quantity, easy processing, biodegradability, natural internal microchannels and a large number of functional groups. Making it into electrode materials is more conducive to large-scale industrial production. Graphene has many excellent properties such as ultra-high current density, ultra-high carrier mobility, chemical inertness, extremely high thermal conductivity, excellent light transmittance, super hydrophobicity, and ultra-high mechanical strength. At the same time, graphene and cellulose have a significant synergistic effect, which can produce an obvious one plus one greater than two effect, so that the hybrid material composed of the two has more excellent electrical and thermal conductivity, mechanical properties, optical properties and other characteristics and functionality. RuO 2It has good electrical conductivity and electrochemical properties, and can provide a large specific surface area and capacitance. During the synthesis process, the aerogel maintains the original skeleton structure, and by regulating the pore structure of the cellulose aerogel, increasing the porosity and the specific surface area of ​​the material, the electrical conductivity is significantly improved. The electrode has good mechanical properties, which avoids uneven mass transfer when the electrolyte flows through the electrode, reduces the concentration polarization of the battery, and thus increases the battery energy output at a given power, and reduces the contact resistance by 30-50%.

[0055] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0056] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a RuO2 / graphene composite cellulose aerogel electrode material, characterized in that: The specific steps include: (i) preparing a cellulose solution: adding cellulose to a pre-cooled cellulose solution and stirring to obtain a cellulose solution; (ii) preparing a graphene oxide / cellulose aerogel composite material: adding a graphene oxide dispersion to the cellulose solution after ultrasonic treatment to obtain a mixed solution, pouring the mixed solution into a mold and freezing it, then adding deionized water into the mold to form a hydrogel, and quickly freezing and drying the hydrogel to obtain a graphene oxide / cellulose aerogel composite material; (iii) preparing graphene composite cellulose carbon aerogel: carbonizing the graphene oxide / cellulose aerogel composite material, cleaning it with a cleaning agent and then drying it to obtain graphene composite cellulose carbon aerogel; (IV) Preparation of RuO2 / graphene composite cellulose aerogel electrode material: Add RuCl3 to a mixture of distilled water and anhydrous ethanol to prepare a RuCl3 solution, add the graphene composite cellulose carbon aerogel to the RuCl3 solution, adjust the pH, collect the precipitate by centrifugation, wash the precipitate, dry and calcine the washed precipitate to obtain a RuO2 / graphene composite cellulose aerogel electrode material.

2. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: The cellulose dissolving solution in step (i) is prepared by mixing NaOH, urea and deionized water in a mass ratio of 7:12:

81.

3. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: In step (i), the mass ratio of cellulose to cellulose dissolving solution is 0.5-5:100, and the precooling temperature is -12°C.

4. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: Step (ii) The preparation method of the graphene oxide dispersion is as follows: graphite powder, NaNO3 powder, concentrated sulfuric acid and phosphoric acid are stirred evenly in an ice bath, and then KMnO4 is slowly added and stirred for 3 hours; the solution is stirred for 2 hours in a 40°C water bath; then distilled water is added, the temperature is raised to 98°C and stirring is continued for 0.5 hours, cooled to room temperature, and then H2O2 is added until the solution turns bright yellow; the product is centrifuged and washed with 10% HCl and distilled water, and precipitated until the pH value of the solution is close to 7, and the obtained graphene oxide is dissolved in distilled water and treated with a 300W ultrasonic cleaner for 60 minutes to obtain the graphene oxide dispersion with a concentration of 0.204-16.32 mg / ml.

5. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: In step (ii), the mass ratio of the graphene oxide dispersion to the cellulose solution is 0.0001-0.008:1, the ultrasonic time is 20 minutes, the freezing temperature is -20°C, and the freezing time is 12 hours.

6. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: The mass ratio of the mixed solution to deionized water in step (ii) is 1:10; the deionized water needs to be replaced every 2 hours, for 5 times.

7. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: The drying in step (ii) is performed by freeze drying, and the drying time is 48 hours.

8. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: The specific steps of the carbonization in step (iii) are as follows: placing the graphene oxide / cellulose aerogel composite material in a tubular furnace, heating the temperature to 700° C. at a heating rate of 5° C. / min under nitrogen protection, and carbonizing for 2 hours; the cleaning agent is composed of hydrochloric acid and deionized water.

9. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: Step (iv) The concentration of RuCl3 in the RuCl3 solution is 0.1Mmol; the mass ratio of the graphene composite cellulose carbon aerogel to the RuCl3 solution is 0.001-0.03:

1.

10. The method for preparing a RuO2 / graphene composite cellulose aerogel electrode material according to claim 1, characterized in that: In step (iv), the pH adjusting agent is 0.3 Mmol potassium hydroxide solution, and the pH needs to be adjusted to 7; the washing agent is a combination of distilled water and anhydrous ethanol; the drying temperature is 60° C. and the time is 12 h; the calcination temperature is 200° C.

Citation Information

Patent Citations

  • Positive electrode of zinc bromine redox flow battery and preparation thereof

    CN102110820A